A Multicenter Evaluation of Different Chemotherapy Regimens in Older Adults With Head and Neck Squamous Cell Carcinoma Undergoing Definitive Chemoradiation - Rühle, Alexander; Weymann, Maria; Behrens, Max; Marschner, Sebastian; Haderlein, Marlen; Fabian, Alexander; Senger, Carolin; Dickstein, Daniel R.; Kraft, Johannes; von der Grün, Jens; Chen, Eric; Aquino-Michaels, Todd; et al. (International Journal of Radiation Oncology Biology Physics, 2024)
Purpose: The number of older adults with head and neck squamous cell carcinoma (HNSCC) is increasing, and treatment of these patients is challenging. Although cisplatin-based chemotherapy concomitantly with radiation therapy is considered the standard regimen for patients with locoregionally advanced HNSCC, there is substantial real-world heterogeneity regarding concomitant chemotherapy in older patients with HNSCC. Methods and Materials: The SENIOR study is an international multicenter cohort study including older patients (≥65 years) with HNSCC treated with definitive radiation therapy at 13 academic centers in the United States and Europe. Patients with concomitant chemoradiation were analyzed regarding overall survival (OS) and progression-free survival (PFS) via Kaplan-Meier analyses. Fine‐Gray competing risk regressions were performed regarding the incidence of locoregional failures and distant metastases. Results: Six hundred ninety-seven patients with a median age of 71 years were included in this analysis. Single-agent cisplatin was the most common chemotherapy regimen (n = 310; 44%), followed by cisplatin plus 5-fluorouracil (n = 137; 20%), carboplatin (n = 73; 10%), and mitomycin C plus 5-fluorouracil (n = 64; 9%). Carboplatin-based regimens were associated with diminished PFS (hazard ratio [HR], 1.39 [1.03-1.89]; P < .05) and a higher incidence of locoregional failures (subdistribution HR, 1.54 [1.00-2.38]; P = .05) compared with single-agent cisplatin, whereas OS (HR, 1.15 [0.80-1.65]; P = .46) was comparable. There were no oncological differences between single-agent and multiagent cisplatin regimens (all P > .05). The median cumulative dose of cisplatin was 180 mg/m2 (IQR, 120-200 mg/m2). Cumulative cisplatin doses ≥200 mg/m2 were associated with increased OS (HR, 0.71 [0.53-0.95]; P = .02), increased PFS (HR, 0.66 [0.51-0.87]; P = .003), and lower incidence of locoregional failures (subdistribution HR, 0.50 [0.31-0.80]; P = .004). Higher cumulative cisplatin doses remained an independent prognostic variable in the multivariate regression analysis for OS (HR, 0.996 [0.993-0.999]; P = .009). Conclusions: Single-agent cisplatin can be considered in the standard chemotherapy regimen for older patients with HNSCC who can tolerate cisplatin. Cumulative cisplatin doses are prognostically relevant in older patients with HNSCC.
CRIS-Team Scopus Importer:2024-01-12

Balancing barriers: Family, career, and gender equality in radiation oncology and radiation research—An interdisciplinary prospective survey among the young workforce - Trommer, Maike; Grohmann, Maximilian; Fabian, Alexander; Ehret, Felix; Hess, Julia; Rückert, Michael; Matschke, Johann; Stefanowicz, Sarah; Rühle, Alexander; Ferdinandus, Simone; Merten, Ricarda; Besserer, Angela; et al. (Strahlentherapie und Onkologie, 2025)
Purpose: There is an urgent need to recruit and retain young professionals in radiation oncology and radiation research as the healthcare system faces major challenges. Our study investigated the experiences and needs of young professionals in this field, focusing on the impact of unpaid care work and gender-related issues. Methods: A web-based survey was created and distributed over a six-week period, featuring one general questionnaire along with three occupation-specific versions tailored for physicians, biologists, and medical physicists involved in radiation oncology and research. Results: Most participants with care responsibilities have temporary contracts, especially female physicians and biologists, while female medical physicists are more likely to hold permanent positions. Research is often conducted outside regular hours, with limited cover arrangements and part-time options varying by field. Key career risks include economic pressure, work-life balance, and uncertain contracts, with employees with care duties feeling less supported overall. In addition, men seem to be more involved in care work and thus face unique challenges, such as insufficient career support and fears of poor future perspective. The study emphasizes the need for strategies to address relevant issues, such as flexible working arrangements, better mentoring support, and clear substitution policies that can ensure that young professionals can balance caring responsibilities with work and career demands. Conclusion: Addressing these challenges is critical for sustaining a diverse and qualified workforce in radiation oncology and radiation research, ensuring excellence in patient care and scientific progress.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Gender; Parity; Radiation oncology; Survey; Young workforce

Benchmarking ChatGPT-4 on a radiation oncology in-training exam and Red Journal Gray Zone cases: potentials and challenges for AI-assisted medical education and decision making in radiation oncology - Huang, Yixing; Gomaa, Ahmed; Semrau, Sabine; Haderlein, Marlen; Lettmaier, Sebastian; Weissmann, Thomas; Grigo, Johanna; Ben Tkhayat, Hassen; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Maier, Andreas; et al. (Frontiers in Oncology, 2023)
Keywords: Large language model; Radiotherapy; Natural language processing; Artificial intelligence; Gray Zone; Clinical decision support (CDS)

CD8+and Regulatory T cells Differentiate Tumor Immune Phenotypes and Predict Survival in Locally Advanced Head and Neck Cancer - Echarti, Alessia; Hecht, Markus; Büttner-Herold, Maike; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2019)
Background: The tumor immune status "inflamed", "immune excluded", and "desert" might serve as a predictive parameter. We studied these three cancer immune phenotypes while using a simple immunohistochemical algorithm. Methods: Pre-treatment tissue samples of 280 patients with locally advanced HNSCC treated with radiochemotherapy were analyzed. A double staining of CD8+ cytotoxic T cells (CTL) and FoxP3+ (Treg) was performed and the cell density was evaluated in the intraepithelial and stromal compartment of the tumor. Results: The classification of tumors as "immune desert" when stromal CTL were <= 50 cells/mm(2), "inflamed" when intraepithelial CTL were > 500 cells/mm(2), and as "excluded" when neither of these definitions met these cut off values allowed the best discrimination regarding overall survival. These groups had median OS periods of 37, 61, and 85 months, respectively. In "immune desert" and "immune excluded" tumors high Treg tended to worsen OS, but in "inflamed" tumors high Treg clearly improved OS. Conclusions: We propose that, in locally advanced HNSCC, the tumor immune state "inflamed", "immune excluded", and "immune desert" can be defined by intraepithelial and stromal CTL. Tregs can further subdivide these groups. The opposing effects of Tregs in the different groups might be the reason for the inconsistency of Tregs prognostic values published earlier.
CRIS-Team WoS Importer:2019-10-25

Classification of three prognostically different groups of head and neck cancer patients based on their metabolic response to induction chemotherapy (IC-1) - Semrau, Sabine; Schmidt, Daniela; Hecht, Markus; Haderlein, Marlen; Kitzsteiner, Christian; Müller, Susanna; Traxdorf, Maximilian; Agaimy, Abbas; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Oral Oncology, 2020)
Objectives: There exist no uniform decision criteria for conservative organ preservation treatments in head and neck cancer patients. Even with 18F-FDG-PET/CT after induction chemotherapy patient selection is challenging. This study correlated metabolic tumor response with treatment types and recurrence patterns. Materials and methods: Decrease in SUVmax in 18F-FDG-PET/CT was measured 21–28 days after IC-1 in 102 patients and correlated to cancer-specific endpoints. Results: Residual SUVmax (resSUVmax) values were uniformly distributed across five cut-off levels (0–0.2 vs. >0.2–0.4 vs. >0.4–0.6 vs. >0.6–0.8 vs. >0.8) containing 20%, 25% 25%, 15% and 15% of patients. Patients were stratified into three response categories according to residual SUVmax (Group A: 0–0.4 = high response Group B: >0.4–0.8 = moderate response, Group C > 0.8 = non-response), 5-year local control rates were 90.5% (Group A) vs. 78.9% (Group B; univariate p = 0.07, multivariate: HR: 3.6, p = 0.03) vs. 49.4% (Group C vs. B; univariate p = 0.04, multivariate: HR 5.5, p < 0.01). After IC-1, Group A received chemoradiotherapy (CRT) only. Group B received surgery plus either (chemo)radiotherapy (B_S + RT/CRT) or chemoradiotherapy (B_CRT), yielding local control rates of 100% and 74.2% (p = 0.11). Group C received surgery plus CRT or CRT alone; both achieved equally poor local control (p = 0.71). Group C had significantly worse distant metastasis-free survival and overall survival than Groups A and B (p < 0.05). Conclusion: Metabolic response after IC-1 differentiates HNC patients into three subgroups predicting local tumor control. Non-response was associated with a poor outcome.
CRIS-Team Scopus Importer:2019-12-03
Keywords: 18F-FDG PET/CT; Chemoradiation; Chemoselection; Head and neck cancer; Hypopharynx; Induction chemotherapy; Larynx; Metabolic response; Resection

Clinical application of breathing-adapted 4D CT: image quality comparison to conventional 4D CT - Werner, René; Szkitsak, Juliane; Madesta, Frederic; Büttgen, Laura; Wimmert, Lukas; Sentker, Thilo; Fietkau, Rainer; Haderlein, Marlen; Bert, Christoph; Gauer, Tobias; Hofmann, Christian (Strahlentherapie und Onkologie, 2023)
Purpose: 4D CT imaging is an integral part of 4D radiotherapy workflows. However, 4D CT data often contain motion artifacts that mitigate treatment planning. Recently, breathing-adapted 4D CT (i4DCT) was introduced into clinical practice, promising artifact reduction in in-silico and phantom studies. Here, we present an image quality comparison study, pooling clinical patient data from two centers: a new i4DCT and a conventional spiral 4D CT patient cohort. Methods: The i4DCT cohort comprises 129 and the conventional spiral 4D CT cohort 417 4D CT data sets of lung and liver tumor patients. All data were acquired for treatment planning. The study consists of three parts: illustration of image quality in selected patients of the two cohorts with similar breathing patterns; an image quality expert rater study; and automated analysis of the artifact frequency. Results: Image data of the patients with similar breathing patterns underline artifact reduction by i4DCT compared to conventional spiral 4D CT. Based on a subgroup of 50 patients with irregular breathing patterns, the rater study reveals a fraction of almost artifact-free scans of 89% for i4DCT and only 25% for conventional 4D CT; the quantitative analysis indicated a reduction of artifact frequency by 31% for i4DCT. Conclusion: The results demonstrate 4D CT image quality improvement for patients with irregular breathing patterns by breathing-adapted 4D CT in this first corresponding clinical data image quality comparison study.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 4D CT; 4D radiotherapy; Image artifacts; Image quality

Combination of growth pattern and tumor regression identifies a high-risk group in neoadjuvant treated rectal cancer patients - Jeßberger, Jonas; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Haderlein, Marlen; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (Journal of Digestive Diseases, 2017)
To analyze the prognostic effect of E-cadherin expression, the growth pattern of the tumor and the regression grade in a rectal cancer cohort treated with neoadjuvant radiochemotherapy (RCT).A total of 223 patients with rectal cancer treated with neoadjuvant RCT followed by surgery were included. Altogether 88 biopsies prior to RCT and 213 tumor resections in an average of 55 days post-RCT were investigated. Protein expression of E-cadherin and tumor growth pattern (solid glandular vs single-cell pattern) was assessed by staining tissue microarrays. The regression grade at the invasion front was determined according to the Dworak scale.There was a significant decrease of E-cadherin expression (P = 0.002) and a significant increased single-cell growth (P < 0.001) at the invasion front in tumor samples after RCT compared with primary biopsies of the tumor. A low E-cadherin expression in the biopsy was related to a longer metastasis-free survival (P = 0.033) and tumor-specific survival (P = 0.030). Post-RCT single-cell growth at the tumor invasion front was a prognostic factor for longer tumor-specific survival (P = 0.021). A combination of growth pattern and the Dworak regression grade was an independent prognostic parameter for tumor-specific survival (P = 0.015).Loss of E-cadherin protein expression in the pretreatment biopsy of rectal cancer is associated with fewer metastases and improved survival. Furthermore, the growth pattern in the post-RCT resection specimen has a prognostic value for survival. A combination of growth pattern and tumor regression score (the RegPat score) showed the highest discriminatory power to identify high-risk patients.
EVALuna2:6858

Comparison of Intrinsic PAM50 Gene Expression Analysis and Immunohistochemical Subtypes of Salivary Duct Carcinoma - Erber, Ramona; Stoehr, Robert; Haller, Florian; Haderlein, Marlen; Hartmann, Arndt; Agaimy, Abbas (LABORATORY INVESTIGATION, 2020)
CRIS-Team WoS Importer:2020-03-24

Complete Remission with consecutive Pneumonitis in metastatic Bronchogenic Carcinoma after combination of Radiotherapy and Nivolumab - Immunological Correlate in peripheral Blood - Hecht, Markus; Donaubauer, Anna-Jasmina; Becker, I.; Rutzner, Sandra; Lubgan, Dorota; Lettmaier, S.; Haderlein, Marlen; Wolf, W.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Deep Learning-based Auto-contouring of Lymph Node Levels in Head and Neck Area - Weissmann, Thomas; Huang, Yixing; Sommer, Phillip; Roesch, Johannes; Mansoorian, Sina; Ayala, H.; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Haderlein, Marlen; Hecht, Markus; Speer, Stefan; Schweizer, Claudia; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

De-intensification of postoperative radiotherapy in head and neck cancer irrespective of human papillomavirus status—results of a prospective multicenter phase II trial (DIREKHT Trial) - Haderlein, Marlen; von der Grün, Jens; Balermpas, Panagiotis; Rödel, Claus; Hautmann, Matthias G.; Steger, Felix; Bohr, Christopher; Hehr, Thomas; Stromberger, Carmen; Budach, Volker; Schymalla, Markus; Engenhart-Cabillic, Rita; et al. (Frontiers in Oncology, 2024)
Background: Current standard treatment concepts in head and neck squamous cell carcinoma (HNSCC) are based on former studies using 2D and 3D treatment plans. However, modern radiation techniques allow for a more precise and individual dose application. Therefore, in a clearly defined patient population, de-intensified risk-adapted radiation is investigated. Methods: Patients with newly diagnosed HNSCC after surgery (with resection margins ≥1 mm and cM0) with the following tumor stages (TNM 7th Edition) were eligible for the study: oral cavity, oropharynx, or larynx: pT1–3, pN0–pN2b; hypopharynx: pT1–2, pN1. The patients should have either a low risk of local recurrence [≤pT2, resection margin ≥5 mm, no peritumoral lymphangiosis (L0), and no perineural invasion] or contralateral lymph node metastasis (≤3 ipsilateral lymph node metastases, in case of well-lateralized oropharyngeal or oral cavity cancer contralateral cN0, otherwise pN0). Patients were assigned to three different treatment regimes with reduction of the treated volume, radiation dose, or both, according to tumor stage and results of surgery performed. The primary objective was to show an LRR of <10% after 2 years. Findings: A total of 150 patients were enrolled. Tumor localizations were as follows: n = 53 (35.3%), oral cavity; n = 94 (62.7%), oropharynx (82% HPV-positive); n = 2 (1.3%), hypopharynx; and n = 1 (0.7%), larynx. A total of 61 patients (41.0%) were stage IVA, 81 (54.0%) were stage III, and 8 (5.3%) were stage II. Median follow-up was 36 months. Cumulative incidence of 2y-LRR was 5.6% (95% CI: 1.7%–9.2%) in the whole study population and 14.1% (95% CI: 3.8%–23.2%) in patients with oral cavity cancer. Cumulative incidence of 2y-LRR in non-irradiated or dose-reduced regions was 3.5% (95% CI: 0.4%–6.5%). After 2 years, disease-free survival was 92% (95% CI: 87%–96%) and overall survival was 94% (95% CI: 90%–98%) for the complete study cohort. Acute III° toxicity was as follows: dysphagia, 30%; xerostomia, 7%; mucositis, 19%; and dermatitis, 4%. Dysphagia and xerostomia decrease over time. After 27 months, late dysphagia III° and xerostomia II° were 1% and 9%, respectively. Interpretation: The study met its primary objective. De-intensification of postoperative radiotherapy irrespective of HPV status in a predefined patient population is associated with a favorable toxicity profile without compromising LRR. In an unplanned subgroup analysis, a significantly increased risk of LRR was observed in patients with oral cavity cancer. In these patients, de-intensified radiotherapy should be applied with caution.
CRIS-Team Scopus Importer:2024-09-13
Keywords: de-intensification; head and neck cancer; HPV; postoperative; radiotherapy

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Dose-dependent deterioration of swallowing function after induction chemotherapy and definitive chemoradiotherapy for laryngopharyngeal cancer - Haderlein, Marlen; Semrau, S.; Ott, O.; Speer, S.; Bohr, Christopher; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
To evaluate the influence of clinical, treatment- and dose-dependent factors on posttreatment swallowing function after induction chemotherapy and definitive chemoradiotherapy in a group of homogeneously treated laryngopharyngeal cancer patients.From 28 May 2008 to 15 February 2013, 45 patients with borderline inoperable laryngopharyngeal cancer that had responded well to induction chemotherapy were treated with definitive chemoradiotherapy. Median follow-up was 22 months. Swallowing function and clinical data were prospectively analyzed using the EORTC QLQ-C30 questionnaire. Swallowing structures were retrospectively delineated on the original treatment planning CT. Dose-volume histograms were calculated for swallowing structures and Dmean, Dmax and V50-V64 values (in 2 Gy increments) were determined for each patient. Tumor volume and infiltration of the swallowing apparatus was defined by CT before induction chemotherapy.Of the 45 patients, 26 (57.8 %) fully regained swallowing function after chemoradiotherapy. A further 12 patients (26.7 %) were able to manage soft, pureed and/or liquid foods; the remaining 7 (15.6 %) were completely dependent on percutaneous endoscopic gastrostomy (PEG). Posttreatment swallowing function was significantly influenced by Dmean to the superior pharyngeal constrictor muscle (PCM, p = 0.041). Correlations between late dysphagia and dose-volume relationships in the superior PCM and soft palate were also observed, which were significant from V60 (p = 0.043) and V58 for the soft palate and superior PCM, respectively. Of the evaluated clinical and tumor-related factors, only alcohol abuse (p = 0.024) had an influence on posttreatment swallowing function.Almost 50 % of patients had deterioration of swallowing function after definitive chemoradiotherapy for laryngopharyngeal cancer. The dose to anatomical structures responsible for swallowing function appears to play a role. Therefore, in selected patients, target volume delineation for radiotherapy of laryngopharyngeal cancer should be optimized on an individual basis to spare the swallowing apparatus.
EVALuna2:18123

Dose Reduction in the Swallowing Area by De-intensification of Radiotherapy in Patients with Head and Neck Cancer in the postoperative Situation - first Plan Analyzes of the DIREKHT Study - Haderlein, Marlen; Speer, Stefan; Hecht, Markus; Merten, Ricarda; Scherl, C.; Semrau, S.; Ott, O.; Fietkau, Rainer (2018)
EVALuna2:36499

Dose reduction to the swallowing apparatus and the salivary glands by de-intensification of postoperative radiotherapy in patients with head and neck cancer: First (treatment planning) results of the prospective multicenter DIREKHT trial - Haderlein, Marlen; Speer, Stefan; Ott, Oliver; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Frey, Benjamin; Scherl, Claudia; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer (Cancers, 2020)
Aim: Evaluating radiotherapy treatment plans of the prospective DIREKHT trial (ClinicalTrials.gov, NCT02528955) investigating de-intensification of radiotherapy in patients with head and neck cancer. Patients and Methods: The first 30 patients from the DIREKHT trial of the leading study centre were included in this analysis. Standard treatment plans and study treatment plans derived from the protocol were calculated for each patient. Sizes of planning target volumes (PTVs) and mean doses to organs at risk were compared using the Student’s t-test with paired samples. Results: Mean PTV3 including primary tumor region and ipsilateral elective neck up to a dose of 50 Gy in the study treatment plans was 662 mL (+/− 165 mL standard deviation (SD)) and therefore significantly smaller than those of the standard treatment plans (1166 mL (+/− 266 mL SD). In the medial and inferior constrictor muscles, cricopharyngeal muscle, glottic and supraglottic laryngeal areas, arytenoid cartilages, contralateral major salivary glands highly significant dose reductions (p < 0.0001) of more than 10 Gy were achieved in study treatment plan compared to standard treatment plan. Conclusion: De-intensification of radiotherapy led to smaller planning target volumes and clinical relevant dose reductions in the swallowing apparatus and in the contralateral salivary glands.
CRIS-Team Scopus Importer:2020-03-06
Keywords: De-intensification; Head neck cancer; Ipsilateral elective neck irradiation only; Postoperative; Radiotherapy; Salivary glands; Swallowing apparatus

Effectiveness of ablative Irradiation of all Metastases versus Irradiation of a singular Metastasis in Combination with Immunocheckpoint Inhibitors - clinical Evaluation of prospective STICI Study - Schubert, P.; Schweizer, C.; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Enhancer hijacking activates oncogenic transcription factor NR4A3 in acinic cell carcinomas of the salivary glands - Haller, Florian; Bieg, Matthias; Will, Rainer; Koerner, Cindy; Weichenhan, Dieter; Bott, Alexander; Ishaque, Naveed; Lutsik, Pavlo; Moskalev, Evgeny; Müller, Susanna; Baehr, Marion; Woerner, Angelika; et al. (Nature Communications, 2019)
The molecular pathogenesis of salivary gland acinic cell carcinoma (AciCC) is poorly understood. The secretory Ca-binding phosphoprotein (SCPP) gene cluster at 4q13 encodes structurally related phosphoproteins of which some are specifically expressed at high levels in the salivary glands and constitute major components of saliva. Here we report on recurrent rearrangements [t(4;9)(q13;q31)] in AciCC that translocate active enhancer regions from the SCPP gene cluster to the region upstream of Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) at 9q31. We show that NR4A3 is specifically upregulated in AciCCs, and that active chromatin regions and gene expression signatures in AciCCs are highly correlated with the NR4A3 transcription factor binding motif. Overexpression of NR4A3 in mouse salivary gland cells increases expression of known NR4A3 target genes and has a stimulatory functional effect on cell proliferation. We conclude that NR4A3 is upregulated through enhancer hijacking and has important oncogenic functions in AciCC.
EVALuna2:35381

Evaluation of Concomitant Systemic Treatment in Older Adults With Head and Neck Squamous Cell Carcinoma Undergoing Definitive Radiotherapy - Rühle, Alexander; Marschner, Sebastian; Haderlein, Marlen; Fabian, Alexander; Weymann, Maria; Behrens, Max; Senger, Carolin; Dickstein, Daniel R.; Kraft, Johannes; von der Grün, Jens; Chen, Eric; Aquino-Michaels, Todd; et al. (JAMA Network Open, 2023)
Importance: The number of older adults with head and neck squamous cell carcinoma (HNSCC) is increasing, and these patients are underrepresented in clinical trials. It is unclear whether the addition of chemotherapy or cetuximab to radiotherapy is associated with improved survival in older adults with HNSCC. Objective: To examine whether the addition of chemotherapy or cetuximab to definitive radiotherapy is associated with improved survival in patients with locoregionally advanced (LA) HNSCC. Design, Setting, and Participants: The Special Care Patterns for Elderly HNSCC Patients Undergoing Radiotherapy (SENIOR) study is an international, multicenter cohort study including older adults (≥65 years) with LA-HNSCCs of the oral cavity, oropharynx/hypopharynx, or larynx treated with definitive radiotherapy, either alone or with concomitant systemic treatment, between January 2005 and December 2019 at 12 academic centers in the US and Europe. Data analysis was conducted from June 4 to August 10, 2022. Interventions: All patients underwent definitive radiotherapy alone or with concomitant systemic treatment. Main Outcomes and Measures: The primary outcome was overall survival. Secondary outcomes included progression-free survival and locoregional failure rate. Results: Among the 1044 patients (734 men [70.3%]; median [IQR] age, 73 [69-78] years) included in this study, 234 patients (22.4%) were treated with radiotherapy alone and 810 patients (77.6%) received concomitant systemic treatment with chemotherapy (677 [64.8%]) or cetuximab (133 [12.7%]). Using inverse probability weighting to attribute for selection bias, chemoradiation was associated with longer overall survival than radiotherapy alone (hazard ratio [HR], 0.61; 95% CI, 0.48-0.77; P < .001), whereas cetuximab-based bioradiotherapy was not (HR, 0.94; 95% CI, 0.70-1.27; P = .70). Progression-free survival was also longer after the addition of chemotherapy (HR, 0.65; 95% CI, 0.52-0.81; P < .001), while the locoregional failure rate was not significantly different (subhazard ratio, 0.62; 95% CI, 0.30-1.26; P = .19). The survival benefit of the chemoradiation group was present in patients up to age 80 years (65-69 years: HR, 0.52; 95% CI, 0.33-0.82; 70-79 years: HR, 0.60; 95% CI, 0.43-0.85), but was absent in patients aged 80 years or older (HR, 0.89; 95% CI, 0.56-1.41). Conclusions and Relevance: In this cohort study of older adults with LA- HNSCC, chemoradiation, but not cetuximab-based bioradiotherapy, was associated with longer survival compared with radiotherapy alone.
CRIS-Team Scopus Importer:2023-03-10

Exploring the Capabilities and Limitations of Large Language Models for Radiation Oncology Decision Support - Putz, Florian; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Fietkau, Rainer; Huang, Yixing (International Journal of Radiation Oncology Biology Physics, 2024)
Keywords: Large language model; GPT-4; Radiation Oncology

Extramedullary plasmacytoma: Tumor occurrence and therapeutic concepts-A follow-up - Holler, Adrian; Cicha, Iwona; Eckstein, Markus; Haderlein, Marlen; Poettler, Marina; Rappl, Anja; Iro, Heinrich; Alexiou, Christoph (Cancer Medicine, 2022)
Background Extramedullary plasmacytoma (EMP) is a solitary tumor consisting of neoplastic plasma cells, with very little to no bone marrow involvement. EMPs are usually located in the head and neck region, but can also occur along the digestive tract, in lungs, or extremities. Methods Following our publication on EMP, which appeared in 1999 (Cancer 85:2305-14), we conducted a literature search for EMP-related reports published between 1999 and 2021. The documented cases, as well as 14 of our own patients from the ENT Clinic Erlangen, were extensively analyzed. Results Between 1998 and 2021, 1134 patients with EMP were reported, for whom information about the tumor localization was available. Among those, 62.4% had EMP in the head and neck area and 37.6% in other body regions. Data on therapy were reported in 897 patients, including 34.3% who received radiation, 28.1% surgery, 22.6% a combination of surgery and radiation, and 15.9% another therapy. In 76.9% patients no recurrence or transformation to multiple myeloma (MM) was reported, 12.8% showed local recurrence and 10.2% developed MM. Radiotherapy alone was associated with a tendency for increased occurrence of MM. In patients with EMP of head and neck area, combination therapy (surgery and radiation) resulted in a 5-year overall survival rate of 98.3%, surgery alone of 92.4%, and radiotherapy of 92.7%. Conclusions Collectively, our analyses indicate that surgical resection alone can achieve long-term tumor control in patients with EMP, if the tumor can be removed within safe limits without causing serious functional impairment. However, if this is not certain, either radiation or a combination of surgery and radiation therapy is suggested as an effective means of local tumor control.
CRIS-Team WoS Importer:2022-05-27
Keywords: extramedullary plasmacytoma; non-Hodgkin lymphoma; survival; therapy; tumor outcomes

Ex Vivo Apoptosis in CD8+ Lymphocytes Predicts Rectal Cancer Patient Outcome - Winkler, Sebastian; Hoppe, Philipp; Haderlein, Marlen; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Gastroenterology Research and Practice, 2016)
Background. Apoptotic rates in peripheral blood lymphocytes can predict radiation induced normal tissue toxicity. We studied whether apoptosis in lymphocytes has a prognostic value for therapy outcome. Methods. Lymphocytes of 87 rectal cancer patients were ex vivo irradiated with 2 Gy, 8 Gy, or a combination of 2 Gy ionizing radiation and Oxaliplatin. Cells were stained with Annexin V and 7-Aminoactinomycin D and apoptotic and necrotic rates were analyzed by multicolor flow cytometry. Results. After treatment, apoptotic and necrotic rates in CD8+ cells are consistently higher than in CD4+ cells, with lower corresponding necrotic rates. Apoptotic and necrotic rates of CD4+ cells and CD8+ cells correlated well within the 2 Gy, 8 Gy, and 2 Gy and Oxaliplatin arrangements (p <= 0.009). High apoptotic CD8+ rates after 2 Gy, 8 Gy, and 2 Gy + Oxaliplatin treatment were prognostically favorable for metastasis-free survival (p = 0.009, p = 0.038, and p = 0.009) and disease-free survival (p = 0.013, p = 0.098, and p = 0.013). Conclusions. Ex vivo CD8+ apoptotic rates are able to predict the patient outcome in regard to metastasis-free or disease-free survival. Patients with higher CD8+ apoptotic rates in the peripheral blood have a more favorable prognosis. In addition to the prediction of late-toxicity by utilization of CD4+ apoptotic rates, the therapy outcome can be predicted by CD8+ apoptotic rates.
EVALuna2:18338

High-grade histology as predictor of early distant metastases and decreased disease-free survival in salivary gland cancer irrespective of tumor subtype - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Uter, Wolfgang; Neukam, Friedrich Wilhelm; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2016)
The purpose of this study was to evaluate risk factors that influence overall survival (OS)/disease-free survival (DFS)/locoregional recurrence-free survival (LRFS), and distant metastases-free survival (DMFS) in patients with high-risk primary salivary gland carcinoma who underwent surgery and postoperative (chemo)radiotherapy with curative intention.We reviewed data of 63 patients with high-risk primary salivary gland carcinoma in a retrospective single-center audit.At a median follow-up of 31 months (range, 5-145 months), cumulative OS and DFS were 91.7%, 77.6%, and 62.9%, and 82.1%, 65.6%, and 57.7%, respectively, after 1, 2, and 5 years. LRFS and DMFS were 92%, 86%, and 86%, and 83.4%, 70.4%, and 62.3% after 1, 2, and 5 years, respectively. Of all patient-related, tumor-related, and treatment-related factors, high-grade histology (G3) was the only factor in univariate and multivariate analysis that was predictive for a shorter DMFS (low/intermediate vs high-grade: 100%, 100%, and 89.4% vs 72.9%, 54.3%, and 42.8% after 1, 2, and 5 years, respectively) and a shorter DFS (low/intermediate vs high-grade: 100%, 90%, and 84.4% vs 71.2%, 50.1%, and 39.4% after 1, 2, and 5 years, respectively) and OS (low/intermediate vs high-grade: 100%, 100%, and 86.5% vs 86.5%, 63.2%, and 46.5% after 1, 2, and 5 years, respectively).High-grade tumor histology is a highly significant predictor of a shorter DMFS, OS, and DFS in salivary gland carcinoma, irrespective of histological subtype. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2041-E2048, 2016.
EVALuna2:5539

High-grade salivary gland cancer: is surgery followed by radiotherapy an adequate treatment to reach tumor control? Results from a tertiary referral centre focussing on incidence and management of distant metastases - Freitag, Viola; Lettmaier, Sebastian; Semrau, Sabine; Hecht, Markus; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Traxdorf, Maximilian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer; Haderlein, Marlen (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: Salivary Gland cancer (SGC) is a rare and heterogenous group of tumors. Standard therapeutic options achieve high local but poor distant control rates, especially in high-grade SGC. The aim of this monocentric study was to evaluate patterns of recurrence and its treatment options (local ablative vs. systemic) in a homogenously treated patient population with high-grade SGC after surgery and radio(chemo)therapy. Methods: Monocentric, retrospective study of patients with newly diagnosed high-grade salivary gland cancer. We retrospectively reviewed clinical reports from 69 patients with high-grade salivary gland cancer in a single-center audit. Survival rates were calculated using the Kaplan–Meier method and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox regression analysis). Results: The median time of follow-up was 31 months. After 5 years, the cumulative overall survival was 65.2%, cumulative incidence of local recurrence was 7.2%, whereas the cumulative incidence of distant metastases was 43.5% after 5 years. 30 of 69 patients developed distant metastases during the time of follow-up, especially patients with adenoid cystic carcinoma, salivary duct carcinoma, adenocarcinoma NOS and acinic cell carcinoma with high-grade transformation. The most common type of therapy therefore was chemotherapy (50%). 85.7% of patients with local ablative therapy of distant metastases show disease progression during follow-up afterwards. Conclusion: With surgery and radio-chemotherapy, a high rate of loco-regional control is reached, but over 40% of patients develop distant metastases in the further follow-up which usually present a diffuse pattern involving in a diffuse metastases. Therefore, in the future, intensified interdisciplinary combination therapies even in the first-line treatment in certain subtypes of high-grade SGC should be investigated.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Chemotherapy; Distant metastases; High-grade; Radiotherapy; Salivary gland cancer

High locoregional Control Rates after Radio (chemo) Therapy in anaplastic Thyroid Carcinoma - a monocentric Analysis - Schmied, M.; Semrau, Sabine; Hecht, Markus; Lettmaier, Sebastian; Mantsopoulos, K.; Traxdorf, Maximilian; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Impact of postoperative radiotherapy and HER2/new overexpression in salivary duct carcinoma : A monocentric clinicopathologic analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Erber, Ramona; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
Retrospective Investigation of the prognostic relevance of clinicopathologic parameters in patients with salivary duct carcinoma (SDC).An experienced pathologist reviewed 67 patients with de novo SDC or SDC ex pleomorphic adenoma. Paraffin-embedded tumor samples were examined by immunohistochemistry for expression of HER2/neu, androgen (AR), progesterone (PR), estrogen (ER), epidermal growth factor (EGFR) and programmed death ligand 1 (PD-L1-R) receptor. In 45 patients who had cM0 and follow-up data available, survival rates were calculated (Kaplan-Meier method) and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox-regression analysis).Overexpression of HER2/neu, AR, ER, PR, EGFR, PD-L1-R was found in 25.4%, 84%, 0%, 0%, 17.9%, 16.4% of patients. Overall (OS), disease-free (DFS), distant-metastases-free survival (DMFS) and locoregional control (LRC) were 92.3/72.4/56.9%, 78.2/58.1/58.1%, 85.4/65.2/65.2% and 89.7/81.9/81.9% after 1/3/5 years (medial follow-up 26 months). In univariate analysis a positive resection margin (p = 0.008) and no postoperative radiotherapy (p = 0.001) predict an increased locoregional recurrence rate. In multivariate analysis only postoperative radiotherapy is statistically significant (p = 0.004). Presence of lymph node metastases, a lymph node density >4 and HER2/neu overexpression predict decreased DFS and DMFS. In multivariate HER2/neu overexpression was the only significant predictor for reduced DFS (p = 0.04) and DMFS (p = 0.02).Postoperative radiotherapy is the only significant predictor for LRC. HER2/neu receptor expression is an independent prognostic factor for decreased DFS and DMFS in patients with SDC. In addition to radio(chemo)therapy, intensified first-line treatment regimens should also be evaluated in the future.
EVALuna2:6895

Increased skin and mucosal toxicity in the combination of vemurafenib with radiation therapy - Merten, Ricarda; Hecht, Markus; Haderlein, Marlen; Distel, Luitpold; Fietkau, Rainer; Heinzerling, Lucie; Semrau, Sabine (Strahlentherapie und Onkologie, 2014)
Palliative radiotherapy is often required for patients with metastatic malignant melanoma in the case of bone or brain metastases. Since BRAF inhibitor therapy is highly efficient in V600-mutated melanomas, there is hesitation to stop it during radiotherapy. Consequently, radiotherapy under simultaneous vemurafenib treatment is frequently needed.We report the case of a patient receiving palliative radiotherapy of spinal bone metastases before and during vemurafenib therapy. The skin reactions were quantitatively scored using computer-assisted digital image evaluation.Radiotherapy without vemurafenib was tolerated very well, whereas radiotherapy under simultaneous vemurafenib treatment resulted in accentuated skin reactions. Furthermore, the patient developed dysphagia and had to be hospitalized for parenteral nutrition. In the quantitative analysis, there was a twofold increase in pigmentation and erythema of the irradiated skin area of the thoracic spine when vemurafenib was combined with radiotherapy compared with radiotherapy treatment alone. This is the first reported case of a patient showing no complications during radiotherapy without vemurafenib but remarkable skin and mucosal toxicity under concurrent vemurafenib therapy. Thus, a genetically conditioned individually elevated radiosensitivity can definitely be excluded. Compared with other reported cases, radiosensitization was not limited to the skin, but also affected the esophageal mucosa.Vemurafenib is a strong radiosensitizer. Patients receiving radiotherapy under simultaneous vemurafenib treatment should be monitored very closely.
EVALuna2:18209

Inflammatory cells infiltrating HPV positive and negative head and neck squamous cell carcinoma - Distel, Luitpold; Farhoumand, D.; Haderlein, Marlen; Fietkau, Rainer (2018)
EVALuna2:36493

Inflammatory Cells in HPV positive and negative Head and Neck Tumors - Distel, Luitpold; Haderlein, Marlen; Farhoumand, D.; Fietkau, Rainer; Hecht, Markus (2018)
EVALuna2:36483

Influence of gender on radiosensitivity during radiochemotherapy of advanced rectal cancer - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Büttner-Herold, Maike; Weber, Klaus; Denz, Axel; Grützmann, Robert; Hartmann, Arndt; Geinitz, Hans; Fietkau, Rainer; et al. (Cancers, 2022)
Gender is increasingly recognized as an important factor in medicine, although it has long been neglected in medical research in many areas. We have studied the influence of gender in advanced rectal cancer with a special focus on radiosensitivity. For this purpose, we studied a cohort of 495 men (84.1% ≥ T3, 63.6% N1, 17.6%, M1) and 215 women (84.2% ≥ T3, 56.7% N1, 22.8%, M1) who all suffered from advanced rectal cancer and were treated with radiochemotherapy. The energy deposited, DNA double-strand break (dsb) repair, occurrence of chromosomal aberrations, duration of therapy, tumor regression and tumor-infiltrating lymphocytes, laboratory parameters, quality of life and survival were assessed. The residual DNA dsb damage 24 h after irradiation in lymphocytes was identical in both sexes. Furthermore, chromosomal aberrations accurately reflecting radiosensitivity, were similar in both sexes. There were no gender-dependent differences in tumor regression, tumor-infiltrating lymphocytes and outcome indicating no differences in the radiosensitivity of cancer cells. The irradiated tumor volume in women was slightly lower than in men, related to body weight, no difference was observed. However, when the total energy deposited was calculated and related to the body weight, women were exposed to higher amounts of ionizing radiation. During radiochemotherapy, decreases in blood lymphocyte counts and albumin and several quality-of-life parameters such as nausea and vomiting, loss of appetite, and diarrhea were significantly worse in women. There is no difference in radiation sensitivity between men and women in both normal tissue and tumors. During radiochemotherapy, the quality of life deteriorates more in women than in men. However, women also recover quickly and there are no long-term differences in quality of life.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Blood values; Deposited energy; DNA double-strand breaks; Gender; Quality of life; Radiochemotherapy; Radiosensitivity; Radiosensitivity; Rectal cancer

Influence of p16 status on indication and outcome of salvage neck dissection in oropharyngeal cancer - Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Semrau, Sabine; Agaimy, Abbas; Eckstein, Markus; Traxdorf, Maximilian; Gostian, Antoniu Oreste; Goncalves, Miguel; Sievert, Matti; Haderlein, Marlen; Grundtner, Philipp; Hecht, Markus; et al. (Acta Oto-Laryngologica, 2020)
Background: Human papillomavirus (HPV)+ and HPV– oropharyngeal squamous cell carcinomas (OPSCC) are separate tumor entities. Aims/Objectives: The aim of this study was to examine if the p16 status influences the need and outcome of a salvage neck dissection (SND) after primary radiochemotherapy (pRCT). Material and methods: Retrospective study of 164 patients (n = 108 p16–, n = 56 p16+) who underwent pRCT for OPSCC between 2009 and 2016. HPV status was defined via p16 immunohistochemical staining. Clinical nodal status was assessed using ultrasound and computed tomography of the neck with contrast. Results: Of the 56 p16+ patients, 17 (30.4%) patients were given an indication for a SND after pRCT with 4 (23.5%) patients showing persistent malignant nodes. Of the 108 p16– patients, 24 (22.2%) patients underwent a SND with 8 (33.3%) patients showing persistent malignant nodes. There was no significant association of the p16 status and neither the indication for SND (p(Chi2(two-sided)-Test) = 0.25, ϕ = 0.34) nor the occurrence of positive nodes (p(Chi2(two-sided)-Test) = 0.74, ϕ = 0.50). The probability for persistence of the ypN + nodal status independent of HPV-status was 29.2%(12/41). Conclusions and significance: There was neither a significant association between the p16 status and the indication for a SND nor for persistent malignant nodal disease after pRCT.
CRIS-Team Scopus Importer:2020-11-06
Keywords: de-escalation; HPV; Oropharyngeal cancer; p16; radiochemotherapy

In head and neck cancer the number of dissected lymph nodes predicts mortality - Haderlein, Marlen; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
EVALuna2:32916

In the Case of Radiochemotherapy of advanced Rectal Cancer, there is only slight gender-related Differences, none in terms of Radiation Sensitivity! - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Geinitz, H.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Is elective irradiation of lymph node levels IV and Vb necessary in nasopharyngeal carcinoma? - Semrau, Sabine; Haderlein, Marlen (Strahlentherapie und Onkologie, 2022)
CRIS-Team WoS Importer:2022-08-26

Is in vivo and ex vivo irradiation equally reliable for individual Radiosensitivity testing by three colour fluorescence in situ hybridization? - Mayo, Theresa; Haderlein, Marlen; Schuster, Barbara; Wiesmueller, Anna; Hummel, Christian; Bachl, Maximilian; Schmidt, Manfred; Fietkau, Rainer; Distel, Luitpold (Radiation Oncology, 2019)
Background Individual radiosensitivity is influencing the outcome of radiation therapy. A general ex vivo testing is very work-intensive. It is of interest to see if a significant prediction concerning the sensitivity can be made by in vivo irradiation during radiation treatment. Methods Blood samples of 274 patients with rectal cancer and 43 lung cancer patients receiving radiotherapy were examined after 2 Gy ex vivo and in vivo ionizing radiation. Chromosomes # 1, 2 and 4 were stained by the 3-color-fluorescence in situ hybridization. Chromosomal aberrations were analyzed as breaks per metaphase (B/M). The deposited energy per session was calculated for each patient. Results Weak correlation could be found between the chromosomal aberrations ex and in vivo. Though receiving significantly smaller deposited energy during radiation therapy (RT) the lung cancer cohort displayed B/M values similar to the rectal cancer cohort. Considering the individual deposit energy differences improved slightly the correlation. Conclusions As various factors influence the induction of chromosomal aberrations it seems not feasible to estimate individual radiosensitivity via in vivo irradiation. An ex vivo estimation of individual radiosensitivity should be preferred.
CRIS-Team WoS Importer:2020-01-10

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
PURPOSE: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1-3, pN0-pN2b), hypopharynx (pT1-2, pN0-pN1), and the indication for postoperative radio(chemo)therapy. PATIENTS AND METHODS: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan-Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. RESULTS: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). CONCLUSION: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
EVALuna2:184476

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
Purpose: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1–3, pN0–pN2b), hypopharynx (pT1–2, pN0–pN1), and the indication for postoperative radio(chemo)therapy. Patients and methods: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan–Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. Results: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). Conclusion: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
CRIS-Team Scopus Importer:2019-06-04
Keywords: Disease-free survival; Late side effect; Overall survival; Radio(chemo)therapy; Second cancer

Lipiodol injections for optimization of target volume delineation in a patient with a second tumor of the oropharynx: A case report - Haderlein, Marlen; Merten, Ricarda; Stojanovic, Andrea; Speer, Stefan; Scherl, Claudia; Fietkau, Rainer; Ott, Oliver J. (Strahlentherapie und Onkologie, 2015)
Lipiodol injections were administered in the head and neck area to improve gross tumor volume (GTV) definition for small-volume re-irradiation of a 63-year-old previously irradiated patient with a second tumor of the oropharynx in the posterior wall with longitudinal ligament infiltration (cT4cN0cM0).The patient had dialysis-depending renal failure. On diagnostic computed tomography (CT), which was performed with intravenous contrast agent, the tumor in the oropharynx was not detectable. Because of dialysis-depending renal failure comorbidity, no contrast agent was applied in the planning CT and in the diagnostic magnetic resonance imaging (MRI) study. In each cross-sectional imaging study performed, the GTV, especially in craniocaudal extensions, was not safely delineable. Therefore, craniocaudal tumor margins were pharyngoscopically marked with Lipiodol injections, an iodine-containing contrast agent.In a second planning CT, the GTV could be defined with the help of the Lipiodol marks and small-volume re-irradiation was performed. No Lipiodol-associated side effects occurred in the patient.In the present case, the use of Lipiodol injections at the tumor margins facilitated the definition of the GTV.
EVALuna2:18277

Long-Term Experience of Chemoradiotherapy Combined with Deep Regional Hyperthermia for Organ Preservation in High-Risk Bladder Cancer (Ta, Tis, T1, T2) - Merten, Ricarda; Ott, Oliver; Haderlein, Marlen; Bertz, Simone; Hartmann, Arndt; Wullich, Bernd; Keck, Bastian; Kühn, Reinhard; Rödel, Claus Michael; Weiss, Christian; Gall, Christine; Uter, Wolfgang; et al. (Oncologist, 2019)
Background: The aim of this study was to evaluate the efficacy and safety of chemoradiotherapy (RCT) combined with regional deep hyperthermia (RHT) of high-risk bladder cancer after transurethral resection of bladder tumor (TUR-BT). Materials and methods: Between 1982 and 2016, 369 patients with pTa, pTis, pT1, and pT2 cN0–1 cM0 bladder cancer were treated with a multimodal treatment after TUR-BT. All patients received radiotherapy (RT) of the bladder and regional lymph nodes. RCT was administered to 215 patients, RCT + RHT was administered to 79 patients, and RT was used in 75 patients. Treatment response was evaluated 4–6 weeks after treatment with TUR-BT. Results: Complete response (CR) overall was 83% (290/351), and in treatment groups was RT 68% (45/66), RCT 86% (178/208), and RCT + RHT 87% (67/77). CR was significantly improved by concurrent RCT compared with RT (odds ratio [OR], 2.32; 95% confidence interval [CI], 1.05–5.12; p =.037), less influenced by hyperthermia (OR, 2.56; 95% CI, 0.88–8.00; p =.092). Overall survival (OS) after RCT was superior to RT (hazard ratio [HR], 0.7; 95% CI, 0.50–0.99; p =.045). Five-year OS from unadjusted Kaplan-Meier estimates was RCT 64% versus RT 45%. Additional RHT increased 5-year OS to 87% (HR, 0.32; 95% CI, 0.18–0.58; p =.0001). RCT + RHT compared with RCT showed a significantly better bladder-preservation rate (HR, 0.13; 95% CI, 0.03–0.56; p =.006). Median follow-up was 71 months. The median number of RHT sessions was five. Conclusion: The multimodal treatment consisted of a maximal TUR-BT followed by RT; concomitant platinum-based chemotherapy combined with RHT in patients with high-grade bladder cancer improves local control, bladder-preservation rate, and OS. It offers a promising alternative to surgical therapies like radical cystectomy. Implications for Practice: Radical cystectomy with appropriate lymph node dissection has long represented the standard of care for muscle-invasive bladder cancer in medically fit patients, despite many centers reporting excellent long-term results for bladder preserving strategies. This retrospective analysis compares different therapeutic modalities in bladder-preservation therapy. The results of this study show that multimodal treatment consisting of maximal transurethral resection of bladder tumor followed by radiotherapy, concomitant platinum-based chemotherapy combined with regional deep hyperthermia in patients with Ta, Tis, T1–2 bladder carcinomas improves local control, bladder-preservation rate, and survival. More importantly, these findings offer a promising alternative to surgical therapies like radical cystectomy. The authors hope that, in the future, closer collaboration between urologists and radiotherapists will further improve treatments and therapies for the benefit of patients.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Bladder cancer; Bladder preservation; Chemoradiotherapy; Hyperthermia; Radiotherapy

Low cytoplasmic and nuclear KPNA2 expression in radiotherapy-treated head and neck squamous cell cancer is associated with an adverse outcome - Erben, Pia; Brunner, Kathrin; Hecht, Markus; Haderlein, Marlen; Buettner-Herold, Maike; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (International Journal of Clinical and Experimental Pathology, 2015)
KPNA2 has effects on carcinogenesis, cell differentiation and transcriptional regulation. KPNA2 has been linked to DNA damage repair by its role to import the DNA double strand break repair complex MRN into the nucleus. The aim of our study was to evaluate the prognostic value of KPNA2 expression in both cytoplasmic and nuclear location in patients with HNSCC treated with radio(chemo)therapy.225 patients with HNSCC treated with neoadjuvant, definitive or adjuvant radio(chemo)therapy were included. Immunohistochemical staining was performed on tissue micro arrays to evaluate nuclear and cytoplasmic KPNA2 expression.The median fraction of tumor cells with nuclear KPNA2 expression was 15%. 47% of tumor samples showed positive cytoplasmic staining. Patients with low nuclear as well as negative cytoplasmic expression tended to have an unfavorable prognosis. There was no correlation between nuclear and cytoplasmic KPNA2 expression. Low nuclear combined with negative cytoplasmic KPNA2 had a clearly unfavorable prognostic effect in local failure-free survival (P=0.014), metastasis-free survival (P=0.001) and no evidence of disease (P=0.008). A combination of low nuclear/negative cytoplasmic with high nuclear/high cytoplasmic KPNA2 expression was prognostically unfavorable with regard to tumor specific survival (P=0.021) and to a lower extent to overall survival (P=0.18). In multivariate analysis low nuclear/negative cytoplasmic versus any high KPNA2 (P=0.008) and T-category (P=0.002) proved as independent prognostic variables.The combination of nuclear and cytoplasmic KPNA2 expression is a potential excellent prognostic parameter in HNSCC treated with radio(chemo)therapy.
EVALuna2:6796

Low-dose radiotherapy of osteoarthritis: from biological findings to clinical effects-challenges for future studies - Weissmann, Thomas; Rückert, Michael; Putz, Florian; Donaubauer, Anna-Jasmina; Hecht, Markus; Schnellhardt, Sören; Schubert, Philipp; Roesch, Johannes; Höfler, Daniel; Ott, Oliver; Haderlein, Marlen; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2023)

Metabolic Response of Short-term Induction Chemotherapy (IC) for Therapy Selection as well as Prediction of long-term local and systemic Therapy Success for Head and Neck cancer. The Results of 100 Patients - Semrau, S.; Haderlein, Marlen; Schmidt, Daniela; Waldfahrer, F.; Scherl, C.; Lettmaier, S.; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer (2017)
EVALuna2:32895

Oligometastatic head and neck cancer: Which patients benefit from radical local treatment of all tumour sites? - Weissmann, Thomas; Höfler, Daniel; Hecht, Markus; Semrau, Sabine; Haderlein, Marlen; Filimonova, Irina; Frey, Benjamin; Bert, Christoph; Lettmaier, Sebastian; Mantsopoulos, Konstantinos; Iro, Heinrich; Fietkau, Rainer; et al. (Radiation Oncology, 2021)
Background: There is a large lack of evidence for optimal treatment in oligometastatic head and neck cancer and it is especially unclear which patients benefit from radical local treatment of all tumour sites. Methods: 40 patients with newly diagnosed oligometastatic head and neck cancer received radical local treatment of all tumour sites from 14.02.2008 to 24.08.2018. Primary endpoint was overall survival. Time to occurrence of new distant metastases and local control were evaluated as secondary endpoints as well as prognostic factors in univariate und multivariate Cox’s regression analysis. To investigate the impact of total tumour volume on survival, all tumour sites were segmented on baseline imaging. Results: Radical local treatment included radiotherapy in 90% of patients, surgery in 25% and radiofrequency ablation in 3%. Median overall survival from first diagnosis of oligometastatic disease was 23.0 months, 2-year survival was 48%, 3-year survival was 37%, 4-year survival was 24% and 5-year survival was 16%. Median time to occurrence of new distant metastases was 11.6 months with freedom from new metastases showing a tail pattern after 3 years of follow-up (22% at 3, 4- and 5-years post-treatment). In multivariate analysis, better ECOG status, absence of bone and brain metastases and lower total tumour volume were significantly associated with improved survival, whereas the number of metastases and involved organ sites was not. Conclusions: Radical local treatment in oligometastatic head and neck cancer shows promising outcomes and needs to be further pursued. Patients with good performance status, absence of brain and bone metastases and low total tumour volume were identified as optimal candidates for radical local treatment in oligometastatic head and neck cancer and should be considered for selection in future prospective trials.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Head and neck cancer; Local treatment; Oligometastatic disease; Radiotherapy; SBRT

Outcome and management of rare high-grade “salivary” adenocarcinoma: the important role of adjuvant (chemo)radiotherapy - Scherl, Claudia; Haderlein, Marlen; Agaimy, Abbas; Mantsopoulos, Konstantinos; Koch, Michael; Traxdorf, Maximilian; Fietkau, Rainer; Grundtner, Philipp; Iro, Heinrich (Strahlentherapie und Onkologie, 2019)
Purpose: To determine survival and management strategies for high-grade adenocarcinoma of salivary glands (ASG). Methods: A retrospective analysis of cases diagnosed between 1998 and 2015 from our single tertiary referral center was performed. Multivariable logistic regression was used to determine factors associated with survival. Results: Thirty-eight cases of high-grade ASG were identified. Most patients were men (68.4%) with a median age of 65.5 years (range 23–84 years). Most tumors were T3 and T4 (65.8%). Regional metastases were common (55.2%), and 42.1% developed distant metastases. The mean follow-up was 60.5 months. All patients received surgery as primary treatment, with 84.2% of patients receiving adjuvant radiation therapy or chemoradiotherapy ([C]RT). Cumulative overall survival was 89.1%, 50.9%, and 20.7% after 1, 5, and 10 years, respectively. Disease-specific survival was 94.4%, 69.8%, and 42.8%, and distant-metastases-free survival (DMFS) was 80.5%, 50.1%, and 40.1% after 1, 5, and 10 years. On multivariable analysis, advanced T status correlated with DMFS (hazard ratio 2.75, 95% CI 0.93–8.16). Postsurgical (C)RT reduced the locoregional recurrence rate by 23.9%, and it improved the locoregional-recurrence-free survival by 39% (p = 0.094). Conclusion: High-grade ASG is considered to have an unfavorable prognosis. Adjuvant (C)RT reduces the rate of locoregional recurrences. Distant metastases are common, and an advanced T stage has increased prognostic value for development of early distant lesions.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Head and neck cancer; Salivary gland cancer; Salivary gland malignancy; Survival salivary gland cancer; Treatment salivary gland cancer

Patterns of care analysis for salivary gland cancer: a survey within the German Society of Radiation Oncology (DEGRO) and recommendations for daily practice - von der Grün, Jens; Roedel, Claus; Semrau, Sabine; Balermpas, Panagiotis; Martin, Daniel; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2021)
Background Salivary gland cancer (SGC) is rare and a heterogeneous type of cancer. Prospective randomized trials are lacking. No guideline focusing on standard procedures of radiotherapy (RT) in the treatment of SGC exists. Therefore, we surveyed the members of the German Society of Radiation Oncology (DEGRO) to gain information about current therapeutic strategies of SGC. Methods An anonymous questionnaire was designed and made available on the online platform umfrageonline.com. The corresponding link was sent to all DEGRO members who provided their user data for contact purposes. Alternatively, a PDF printout version was sent. Frequency distributions of responses for each question were calculated. The data were also analyzed by type of institution. Results Sixty-seven responses were received, including answers from 21 university departments, 22 non-university institutions, and 24 radiation oncology practices. Six participants reported that their departments (practice: n = 5, non-university hospital: n = 1) did not treat SGC, and therefore the questionnaire was not completed. Concerning radiation techniques, target volume definition, and concomitant chemotherapy, treatment strategies varied greatly among the participants. Comparing university vs. non-university institutions, university hospitals treat significantly more patients with SGC per year and initiated more molecular pathological diagnostics. Conclusion SGC represents a major challenge for clinicians, as reflected by the inhomogeneous survey results regarding diagnostics, RT approaches, and systemic therapy. Future prospective, multicenter clinical trials are warranted to improve and homogenize treatment of SGC and to individualize treatment according to histologic subtypes and risk factors.
CRIS-Team WoS Importer:2021-09-03

PD-L1 is upregulated by radiochemotherapy in rectal adenocarcinoma patients and associated with a favourable prognosis - Hecht, Markus; Buettner-Herold, Maike; Erlenbach-Wuensch, Katharina; Haderlein, Marlen; Croner, Roland; Grützmann, Robert; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (European Journal of Cancer, 2016)
The influence of neoadjuvant radiochemotherapy (RCT) on programmed death-ligand 1 (PD-L1) expression, a predictive marker for programmed cell death protein 1 (PD-1) inhibitor therapy, was studied on tumour and inflammatory cells in rectal adenocarcinoma patients along with its prognostic value.PD-L1 immunohistochemistry was performed on tissue microarrays of 103 pre-RCT biopsies and 159 post-RCT surgical specimens (central tumour, invasive front and normal tissue) of 199 patients. In 63 patients, both samples were available. Proportion and maximum intensity of PD-L1-positive (PD-L1+) cells were evaluated.RCT increased the proportion of PD-L1-expressing cancer cells from 2.1% to 7.8% in the central tumour (p < 0.001) or 9.3% in the invasive front (p < 0.001). Cancer cell PD-L1 on its own could not predict prognosis. High PD-L1 expression on pre-RCT inflammatory cells (maximum intensity: p = 0.048) and post-RCT invasive front inflammatory cells (p = 0.010) correlated with improved no evidence of disease survival. In multivariate analysis, the combination of low PD-L1 in cancer and inflammatory cells was an independent negative prognostic marker for overall survival (OS) pre-RCT (Cox's proportional hazard ratio 0.438, p = 0.045) and in the invasive front post-RCT (Cox's proportional hazard ratio 0.257, p = 0.030).Neoadjuvant RCT is associated with an increased PD-L1 expression in rectal adenocarcinoma patients, which should prompt clinical trials combining radiotherapy and PD-1/PD-L1 pathway blockade. Combined low PD-L1 expression on tumour and inflammatory cells is an independent negative prognostic marker for OS in RCT of rectal adenocarcinoma.
EVALuna2:6814

Pilot Project for App-based Patient Connection in outpatient Tumor Therapy - Hecht, Markus; Goldbrunner, L.; Kaul, F.; Winkler, S.; Ploner, N.; Lettmaier, Sebastian; Haderlein, Marlen; Kallies, Annett; Pirschel, Wiebke; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Positive factors on survival of head and neck cancer of unknown primary: what the clinician can do - Khalil, Firas; Koch, Michael; Iro, Heinrich; Sievert, Matti; Haderlein, Marlen; Semrau, Sabine; Fietkau, Rainer; Agaimy, Abbas; Scherl, Claudia (Acta Oto-Laryngologica, 2023)
Background: Management of patients with head and neck cancer of unknown primary (HNCUP) is challenging. Aims/Objectives: To provide a long-term analysis focusing on protective survival factors for clinical decision-making. Furthermore, the prognostic value of the current N classification system was evaluated. Material and methods: We retrospectively analyzed patients with HNCUP between 2003 and 2016. Univariate and multivariate analyses were used to investigate predictors of overall survival (OS). Results: A primary tumor was found in 67 of 290 patients with suspected HNCUP, leaving after exclusion 141 HNCUP cases for analysis, who received multi-step therapy (MST) (n = 108) or single therapy (n = 28). Chemotherapy (CT) (n = 101), curative MST, ≤3 positive lymph nodes (LN) (n = 33), squamous cell carcinoma (SCC) (n = 123), HPV+ (n = 21), M0 (n = 70) increased OS by 21.8%, 24.4%, 12.7%, 6.8%, 18.7%, 29.6%, respectively. 5- and 10-year OS was 78.1%/66.6%. The number of metastatic LNs predicted OS is better than N classification. Conclusion and significance: Aspects for clinical decision-making: Curative MST and SCC histology were the most significant predictors for improved OS. Categorizing LN into 1, 2-3, and >3 LNs was more significant than the traditional N classification. The addition of CT to curative MST has a stronger impact on survival than HPV and N classifications.
CRIS-Team Scopus Importer:2023-10-27
Keywords: cancer; cancer of unknown primary; CUP; head and neck; hNCUP; hNSCC; squamous cell carcinoma; survival

Pradictive Character of Immunophenotyping in peripheral Blood in Patients treated with PD-1 Immunocheckpoint Inhibitors with and without Radiotherapy (Prospective Phase IV Study ST-ICI) - Hecht, Markus; Donaubauer, Anna-Jasmina; Harrer, A.; Rutzner, Sandra; Becker, I.; Lettmaier, S.; Haderlein, Marlen; Wolf, W.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36500

Predicting cisplatin tolerability in older adults with head and neck cancer – Insights for improved chemoradiation outcomes - Rühle, Alexander; Weymann, Maria; Behrens, Max; Olbrich, Johannes; Kut, Carmen; Marschner, Sebastian N.; Haderlein, Marlen; Fabian, Alexander; Senger, Carolin; Bakst, Benjamin P.; Kraft, Johannes; von der Grün, Jens; et al. (Radiotherapy and Oncology, 2025)
Purpose: Cumulative cisplatin doses of ≥ 200 mg/m2 improve survival in adults with head-and-neck squamous cell carcinoma (HNSCC) undergoing chemoradiation, but many older adults with HNSCC cannot receive this prognostically relevant dose due to toxicities. This study aims to develop predictive models to assess the likelihood of older adults with HNSCC receiving ≥ 200 mg/m2 cisplatin during chemoradiation. Methods: 366 patients from the SENIOR database, an international cohort of adults ≥ 65 years with HNSCC, received definitive chemoradiation with single-agent cisplatin and were analyzed. A Generalized Linear Model (GLM), Support Vector Machine (SVM), and Random Forest Model (RFM) were trained and compared for their performance in predicting a cumulative cisplatin dose of ≥ 200 mg/m2. Results: 195 (53 %) patients achieved a cumulative cisplatin dose of ≥ 200 mg/m2. In the GLM, laryngeal carcinoma (β = 1.37, p = 0.01), tumoral p16 positivity (β = 0.69, p = 0.04), higher hemoglobin levels (β = 0.26, p = 0.002), elevated C-reactive protein (CRP) concentration (β = 0.02, p = 0.003), and increased estimated glomerular filtration rate (eGFR) (β = 0.02, p = 0.008) were associated with a higher probability of reaching ≥ 200 mg/m2 cisplatin. Hemoglobin, CRP, eGFR, and p16 status constituted the most important features in the SVM and RFM. AUC values for the GLM, SVM, and RFM were 0.70 (95 % CI, 0.67–0.73), 0.71 (95 % CI, 0.68–0.73), and 0.73 (95 % CI, 0.71–0.75), respectively. Conclusions: We developed predictive models to support clinicians in identifying older adults with HNSCC capable of tolerating ≥ 200 mg/m2 cumulative cisplatin during chemoradiation. Once validated, these models could improve personalized treatments and enhance shared decision-making in older adults with HNSCC.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chemotherapy; Cisplatin; Elderly; Geriatric; Head-and-neck cancer; Radiotherapy

Prognostic Significance of immune-associated Side Effects under Radioimmunotherapy and Immunotherapy alone in Patients of the prospective ST-ICI Study - Schweizer, C.; Schubert, P.; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Becker, Ina; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Progress Patterns under Radioimmunotherapy - clinical Evaluation of the prospective STICI Study - Schubert, Philipp; Schweizer, Claudia; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective Assessment of the Inflammation Parameters in Blood Counts and Blood Serum as prognostic/predictive Parameters for Treatment with Immune Checkpoint-Inhibitors - Schweizer, Claudia; Haderlein, Marlen; Schubert, Philipp; Zhou, Jianguo; Semrau, Sabine; Rutzner, Sandra; Gostian, Antoniu-Oreste; Frey, Benjamin; Donaubauer, Anna-Jasmina; Eckstein, Markus; Becker, Ina; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective Evaluation of All-lesion Versus Single-lesion Radiotherapy in Combination With PD-1/PD-L1 Immune Checkpoint Inhibitors - Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Schweizer, Claudia; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Zhou, Jianguo; Gaipl, Udo; Fietkau, Rainer; et al. (Frontiers in Oncology, 2020)
Background: Local ablative treatments improve survival in patients with oligometastatic disease in addition to chemotherapy. The application of immune checkpoint inhibitors prolonged patients’ survival in different tumor entities. This raises the question if patients still benefit from intensified local treatments in combination with a more efficient systemic treatment with immune checkpoint inhibitors. Methods: The prospective non-interventional ST-ICI trial investigates treatment with PD-1/PD-L1 (Programmed cell death protein 1/Programmed cell death 1 ligand 1) immune checkpoint inhibitors and radiotherapy in different tumor entities. Patients who started radiotherapy and immunotherapy concomitantly were included in this interim analysis. In this cohort patients with all-lesion radiotherapy (all tumor lesions irradiated, al-RT) were compared to patients with radiotherapy to only a single of their tumor lesions (single-lesion radiotherapy, sl-RT). Endpoints of the interim analysis were progression-free survival (PFS), overall survival (OS) and time to progression (TTP). Results: A total of 104 patients were registered between April 2017 and August 2019. Fifty patients started immune checkpoint inhibitor treatment and radiotherapy concomitantly and were included. Most frequent tumor entities were non-small cell lung cancer (62%) followed by head and neck squamous cell cancer (26%). Most frequent location of radiotherapy was lung (34%) and central nervous system (20%). Median duration of follow-up was 8.6 months beginning with first administration of the immune-checkpoint-inhibitor. Median PFS was 9.2 months (95% CI, 5.8 – 12.6) in the al-RT group and 3.0 months (95% CI, 2.5 – 3.5) in the sl-RT group (p<0.001). Median OS was 11.6 months (95% CI, 8.1 - 15.1) in the al-RT group and 4.2 months (95% CI, 3.0 - 5.4) in the sl-RT group (p=0.007). Median TTP was not reached in the al-RT group compared to 4.6 months (95% CI, 1.1–8.0) in the sl-RT group (p=0.028). Univariate Cox regression analyses computed tumor entity, histology, central nervous system metastases, immunotherapy drug and al-RT as predictors of OS (with an effect p-value of ≤ 0.1). In the multivariable analysis only tumor entity and al-RT remained prognostic factors for OS. Conclusion: Patients with PD-1/PD-L1 immune checkpoint inhibitor therapy benefit from local radiotherapy to all known lesions compared to single-lesion radiotherapy regarding PFS and OS.
CRIS-Team Scopus Importer:2020-11-20
Keywords: all-lesion; immune checkpoint inhibitors; immunotherapy; oligometastatic; radiotherapy; single-lesion

Prospective evaluation of the prognostic value of immune-related adverse events in patients with non-melanoma solid tumour treated with PD-1/PD-L1 inhibitors alone and in combination with radiotherapy - Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Frey, Benjamin; Gaipl, Udo; Zhou, Jianguo; Fietkau, Rainer; et al. (European Journal of Cancer, 2020)
Background: Prospective data about the prognostic value of immune-related adverse events (irAEs) in non-melanoma solid tumours are rare. The prognostic value of irAEs in patients treated with combined radiotherapy and immunotherapy is currently unknown. Patients and methods: The prospective non-interventional ST-ICI trial investigates treatment response of tumour patients to anti–programmed cell death-ligand 1 (PD-L1) immune checkpoint inhibitors alone and in combination with radiotherapy and possible predictive markers. Patients undergoing immunotherapy or immunoradiotherapy were surveyed for irAEs. Results: A total of 104 patients were included of whom 29 patients (28%) developed irAEs. Additional radiotherapy was performed in 50 patients (48%). Main tumour entities within the entire cohort were non–small cell lung cancer (NSCLC) (44%) and head and neck squamous cell carcinoma (42%). The rate of irAEs did not differ in patients with and without radiotherapy (p = 0.668). Patients who developed irAEs had longer overall survival (OS) (median: 22.8 months versus 9.0 months without irAEs, p = 0.001) and progression-free survival (PFS) (median: 7.8 months versus 3.2 months without irAEs, p = 0.002). In the subgroup with combined radiotherapy, patients with irAEs also had longer OS (median: 22.8 months versus 7.1 months without irAEs, p = 0.005) and PFS (median: 8.8 months versus 3.0 months without irAEs, p = 0.005). On multivariate analysis only PD-L1 on tumour cells (p = 0.049) and irAEs (p = 0.001) remained independent predictors of OS. Conclusion: The development of irAEs represents a favourable prognostic parameter in patients undergoing immunotherapy and immunoradiotherapy for solid tumours.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Non-melanoma solid tumours; Prognostic parameters; Radiotherapy

Questionnaire-based detection of immune-related adverse events in cancer patients treated with PD-1/PD-L1 immune checkpoint inhibitors - Griewing, Luisa Maria; Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Haderlein, Marlen; Weissmann, Thomas; Semrau, Sabine; Gostian, Antoniu Oreste; Müller, Sarina Katrin; Traxdorf, Maximilian; et al. (BMC Cancer, 2021)
Background: Immune checkpoint inhibitors (ICI) have become standard treatment in different tumor entities. However, safe treatment with ICI targeting the PD-1/PD-L1 axis requires early detection of immune-related adverse events (irAE). There exist different questionnaires of drug manufacturers for the detection of irAE that have not been validated so far. Methods: The prospective non-interventional ST-ICI trial studied treatment with PD-1/PD-L1 ICI alone or combined with radiotherapy. In the current analysis, the detection rate of self-reported irAE with a patient questionnaire containing 41 different questions was compared to clinician-reported irAE. Results: Between April 2017 and August 2019, a total of 104 patients were prospectively enrolled. NSCLC (44%) and HNSCC (42%) were the most frequent tumor entities. A total of 784 questionnaires were collected. A total of 29 irAE were reported by clinicians. The most frequent irAE was hypothyroidism (9%), followed by skin reactions (5%), hepatitis (4%), diarrhea (3%), and pneumonitis (3%). Questions that became significantly more often positive at time points of clinician-reported irAE were “weight change”, “difficulty to grip things”, “bloody or mucous stool” and “insomnia”. Self-reported organ-specific questions detected at least 50% of clinician-reported irAE of gastrointestinal, lung, endocrine, and skin irAE. It was not possible to detect hepatic irAE with the questionnaire. Conclusion: Questionnaires can help to detect gastrointestinal, lung, endocrine, or skin irAE, but not hepatic irAE. Questions on “weight change” and “insomnia” may help to increase the detection rate of irAE, besides organ-specific questions. These results are a valuable contribution to the future development of a specific and practicable questionnaire for early self-reported detection of irAE during ICI therapy in cancer patients. Trial registration: ClinicalTrials.gov, NCT03453892. Registered on 05 March 2018.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Patient-reported irAE; PD-1; PD-L1; Questionnaire; Side effects; Solid tumors; Toxicity

Radio(chemo)therapy in anaplastic thyroid cancer—high locoregional but low distant control rates—a monocentric analysis of a tertiary referral center - Schmied, Matthias; Lettmaier, Sebastian; Semrau, Sabine; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2022)
Background: Anaplastic thyroid cancer (ATC) is a lethal disease with highly aggressive disease progression. This study analyses the influence of radio(chemo)therapy, R(C)T, on disease control, survival rates and predictors for survival. Patients and methods: A total of 33 patients with ATC, treated at a tertiary referral center between May 2001 and April 2020 were included. Univariate and multivariate analysis were used to investigate correlates of R(C)T and predictors on disease control and survival rates. Results: Median follow-up was 4 months. In UICC stage IVA and IVB median overall survival (OS) was 8 months, median progression-free survival (PFS) was 6 months. Patients with UICC stage IVA and IVB and patients being irradiated with a radiation dose of more than 60 Gy showed increased OS. Of these patients, 3 were alive and free from disease. All of them receiving cisplatin-based radiochemotherapy and a minimum radiation dose of 66 Gy. UICC stage IVC showed a median OS of 2.5 months and a median PFS of 1 month. Only 2 of 16 patients had local failure. Conclusion: Depending on UICC stage, RT with high radiation dose can lead to improved OS or at least higher locoregional control. A limiting factor is the high incidence of distant metastases; therefore modern systemic treatment options should be integrated into multimodal therapy concepts.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Anaplastic thyroid cancer; Chemotherapy; Multimodal treatment; Radiation dose; Radiotherapy

Radiotherapy for the elderly Patient with Head and Neck Squamous Cell Carcinoma - Experience of a Center for ENT-Tumors - Winkler, Leah-Sophie; Lettmaier, Sebastian; Semrau, Sabine; Müller, Sarina Katrin; Traxdorf, Maximilian; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Reduction of elective radiotherapy treatment volume in definitive treatment of locally advanced head and neck cancer—comparison of a prospective trial with a revised simulated contouring approach - Weissmann, Thomas; Speer, Stefan; Putz, Florian; Lettmaier, Sebastian; Schubert, Philipp; Shariff, Maya; Semrau, Sabine; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Müller, Sarina Katrin; Eckstein, Markus; Hautmann, Matthias; et al. (Journal of Clinical Medicine, 2021)
Definitive radiochemotherapy of locally advanced head and neck squamous cell cancer (HNSCC) achieves high locoregional tumor control rates; but is frequently associated with long-term toxicity. A future direction could be a de-escalation strategy focusing on treated volume rather than radiotherapy dose. This analysis evaluates radiotherapy dose and volume parameters of patients treated with a standard contouring approach in a clinical trial context compared with a revised volume-reduced contouring approach. In this case, 30 consecutive patients from the CheckRad-CD8 trial treated at a single study center were included in this analysis. Treatment toxicity and quality of life were assessed at the end of radiotherapy. Standard treatment plans (ST) following state of the art contouring guidelines that were used for patient treatment and volume reduced treatment plans (VRT) according to a revised simulated approach were calculated for each patient. Planning target volumes (PTV) and mean doses to 38 organs-at-risk structures were compared. At the end of radiotherapy patients reported high rates of mucositis; dysphagia and xerostomia. In addition; patient reported quality of life as assessed by the EORTC QLQ-HN35 questionnaire deteriorated. Comparing the two contouring approaches; the elective PTV_56 Gy and the high risk PTV_63 Gy (shrinking field) were significantly smaller in the VRT group. Significant reduction of mean dose to structures of the oral cavity; the larynx as well as part of the swallowing muscles and the submandibular glands was achieved in the simulated VRT-plan. Treatment de-intensification by reduction of the irradiated volume could potentially reduce treatment volume and mean doses to organs at risk. The proposed contouring approach should be studied further in the context of a clinical trial.
CRIS-Team Scopus Importer:2021-10-22
Keywords: De-intensification; Definitive treatment; Head neck cancer; Radiotherapy; Salivary glands; Swallowing function; Volume reduc-tion

Regulatory T cells and cytotoxic T cells close to the epithelial–stromal interface are associated with a favorable prognosis - Rudolf, Julian; Büttner-Herold, Maike; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Jeßberger, Jonas; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (OncoImmunology, 2020)
Cytotoxic T cells and regulatory T cells play a crucial role in the outcome of cancer patients. Besides the density of these cells, it was shown recently that the spatial distribution is equally important. Here, we specifically analyzed the spatial distribution of these T cell subtypes at the epithelial–stromal interface in a rectal cancer cohort and its relevance for prognosis. We studied a cohort of 191 patients with advanced rectal cancer treated by radiochemotherapy (RCT). Tissue microarrays were immunohistochemical double-stained by FoxP3+ and CD+. Cell densities were analyzed in the stromal and epithelial compartment. Additionally, an image analysis software calculated the distances of lymphocytes to the epithelial–stromal interface (ESI). CD8+ and FoxP3+ cell counts decreased clearly after RCT with the decrease of FoxP3+ being more pronounced than of CD8+ cells. In the invasive front, short distances of the ESI to CD8+ and to FoxP3+ cells were associated with improved overall survival. Cell counts in the stromal compartment had no influence on prognosis. No correlation between stromal and epithelial lymphocyte densities was observed. The distance of epithelial–stromal interface to CD8+ and FoxP3+ cells was more accurate in predicting prognosis in the stromal compartment of rectal cancer patients than mere cell counts and could thereby be means of better stratifying patients for therapy. This observation will have to be validated in future prospective studies with regard to other tumor entities and its implications for the responsiveness of tumors to new therapeutic modalities.
CRIS-Team Scopus Importer:2020-04-28
Keywords: epithelial–stromal interface; rectal cancer; regulatory T cells; spatial distribution; ﻿cytotoxic T cells

Repeating of local therapy of distant metastases increases overall survival in patients with synchronous metastasized rectal cancer-a monocentric analysis - Haderlein, Marlen; Lettmaier, Sebastian; Langheinrich, Melanie; Schmid, Axel; Semrau, Sabine; Hecht, Markus; Beck, Michael; Schmidt, Daniela; Grützmann, Robert; Fietkau, Rainer; Denz, Axel (International Journal of Colorectal Disease, 2018)
PURPOSE: The aim was to evaluate the outcome of treatment-naive patients with synchronous metastatic rectal cancer after chemotherapy with FOLFOXIRI followed by local therapeutic procedures of all tumor lesions as complete as possible. METHODS: We reviewed data of 30 patients with synchronous distant metastatic rectal cancer who underwent chemotherapy with FOLFOXIRI and subsequent local therapy in our institution. RESULTS: Median follow-up was 28 months (range: 8; 74). Cumulative overall survival (OS) and progression-free survival (PFS) was 93.3, 76.9, 55.6% and 46.2, 29.7, 29.7% after 1, 2, 4 years. Non-response to chemotherapy with FOLFOXIRI was associated with a highly significant decreased OS (p < 0.0001). The consistent use of local ablative procedures led to a statistically significant increase in OS (p < 0.0001), but not in PFS (p = 0.635). Patients with ≤ 4 distant metastases showed a better OS (p = 0.033). CONCLUSIONS: Response to intensified first-line chemotherapy with FOLFOXIRI, treatment of the primary rectal tumor, and repeated thorough local ablative procedures in patients with synchronous metastasized rectal cancer may lead to long-term survival, even in a subset of patients with unresectable disease at initial diagnosis.
EVALuna2:36458

Response to 6 cycles of chemotherapy with FOLFIRINOX is predictive of overall survival in patients with locally advanced unresectable pancreatic cancer - Haderlein, Marlen; Lubgan, Dorota; Lettmaier, S.; Semrau, S.; Wolf, W.; Golcher, H.; Hohenberger, Werner; Fietkau, Rainer (2016)
EVALuna2:15236

Salivary gland carcinoma (SGC) with perineural spread and/or positive resection margin - High locoregional control rates after photon (chemo) radiotherapy - Experience from a monocentric analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Putz, Florian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Radiation Oncology, 2019)
Background: The aim was to evaluate the outcome, especially locoregional control of patients with locally advanced salivary gland carcinoma (SGC) with perineural spread (Pn1) and/or positive resection margins (R1/2) after postoperative photon (chemo) radiotherapy in a single centre. Methods: We retrospectively reviewed data of 65 patients with newly diagnosed locally advanced SGC without distant metastases who underwent radio (chemo) therapy in the department of radiation oncology of the university hospital of Erlangen from January 2000 until April 2017. Kaplan Meier method was used to calculate survival and recurrence rates. In univariate analysis the log-rank test was used to correlate patient-/tumor- and treatment-related parameters to survival and recurrence rates. Results: Median follow-up was 45 months (range: 6; 215). After 1, 3, 5 years cumulative incidence of local and locoregional failure was 3.1, 7.0, 7.0% and 3.1, 9.7, 12.9%, whereas cumulative incidence of distant metastases (DM) was 15.6, 36.0, 44.0%. After 1,3, 5 years cumulative Overall (OS) and Disease-free survival (DFS) was 90.5, 74.9, 63.9% and 83.0, 54.8, 49.4%. The only significant predictor for decreased local and locoregional control was a macroscopic resection margin(R2) (p = 0.002 and p = 0.04). High-grade histology (p = 0.006), lymph node metastases with extracapsular spread (p = 0.044) and an advanced T-stage (p = 0.031) were associated with an increased rate of DM. High-grade histology was the only factor predicting for a decreased DFS (p = 0.014). Conclusion: Photon radiotherapy leads to high local and locoregional control rates in a high-risk patient population with SGC with microscopically positive resection margins and/or perineural spread. The most common site of disease recurrence was distant metastases. Therefore the real challenge for the future should be to prevent distant metastases.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Locoregional control; Perineural spread; Photon radiotherapy; Positive resection margin; Salivary gland cancer

Secondary Tracheoesophageal Puncture After Laryngectomy Increases Complications With Shunt and Voice Prosthesis - Scherl, Claudia; Kauffels, Julia; Schützenberger, Anne; Döllinger, Michael; Bohr, Christopher; Dürr, Stephan; Fietkau, Rainer; Haderlein, Marlen; Koch, Michael; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller, Sarina Katrin; et al. (Laryngoscope, 2020)
Objectives/Hypothesis To evaluate the demographics, clinical features, management, and prognostic indicators of tracheoesophageal puncture complications in patients undergoing placement of voice prosthesis following cancer treatment.
CRIS-Team WoS Importer:2020-02-21

Single-cycle induction chemotherapy before chemoradiotherapy or surgery in functionally inoperable head and neck squamous cell carcinoma: 10-year results - Breheret, Marius; Lubgan, Dorota; Haderlein, Marlen; Hecht, Markus; Traxdorf, Maximilian; Schmidt, Daniela; Müller, Sarina Katrin; Kitzsteiner, Christian; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer; Semrau, Sabine (European Archives of Oto-Rhino-Laryngology, 2019)
Introduction The response to induction chemotherapy (IC) predicts local control after conservative treatment of laryngeal, meso- and hypopharyngeal head and neck squamous cell carcinoma (HNSCC) and can thus help to avoid surgery. Single-cycle induction chemotherapy may help to maintain a low local recurrence rate while keeping the overall toxicity manageable. However, long-term data on single-cycle IC response by tumor location is lacking. Methods N = 102 patients with functionally inoperable primary HNSCC of the larynx (n = 43), hypopharynx (n = 42) or mesopharynx/tongue (n = 17) received one cycle of docetaxel (75 mg/m(2), d1) plus cisplatin (30 mg/m(2), d1-3) or carboplatin (AUC 1.5, d1-3) and a response evaluation 3 weeks later. Responders (>= 30% tumor size reduction and >= 20% SUVmax decrease in F-18-FDG PET/CT) were recommended chemoradiotherapy (CRT), and non-responders surgery. Results The overall response rate was 72.5%. All 74 responders and 10 non-responders received primary CRT, and 18 patients received primary surgery after single-cycle IC. Overall 10-year local recurrence-free survival (LRFS) was 73.7%. Three-year LRFS was 88.2% (mesopharynx/tongue), 88.2% (larynx), and 73.3% (hypopharynx); p = 0.17. 3-year distant metastasis-free survival (DMFS) was 94.1% (mesopharynx/tongue), 88.0% (larynx) and 76.4% (hypopharynx); p > 0.05. This influenced the 3-year cancer-specific survival (CSS) for larynx (91.2%) vs. hypopharynx tumors (60.8%); p = 0.003, but CSS was not different to tumors in the mesopharynx/tongue (81.4%); p > 0.05. Conclusions A single-cycle induction chemotherapy for HNSCC enables surgery plus adjuvant therapy as well as chemoradiotherapy. The long-term local and distant disease control was good but varied between tumors in the larynx and mesopharynx/tongue vs. hypopharynx.
CRIS-Team WoS Importer:2019-10-18

Single-cycle induction chemotherapy followed by chemoradiotherapy or surgery in patients with head and neck cancer: What are the best predictors of remission and prognosis? - Semrau, Sabine; Haderlein, Marlen; Schmidt, Daniela; Lell, Michael; Wolf, Walburga; Waldfahrer, Frank; Uder, Michael; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Cancer, 2015)
There is controversy over the concept of function and organ preservation by chemotherapy/chemoradiation instead of surgery in locally advanced cancer of the larynx or pharynx. Tumor response to induction chemotherapy (ICT) can help in choosing between conservative and surgical treatment. This study compared 3 methods of assessing response to ICT: endoscopy, computed tomography, and (18) F-FDG-PET/CT.Primary response to 1 cycle of ICT with docetaxel plus platinum was assessed by the aforementioned methods in 62 laryngopharyngeal cancer patients. Endoscopic response was the deciding factor for selecting further treatment: surgery for endoscopic nonresponders (<30% tumor response) versus chemoradiotherapy for endoscopic responders.ICT achieved endoscopic response in 48 of 62 patients (77%). Individual relative residual tumor activity of standardized uptake value (resSUVmax ) in (18) F-FDG-PET/CT was a median 0.38 of baseline (0.09-1.71), whereas residual tumor extent in CT (resCT) was 0.75 of baseline (0.32-1.20). Endoscopic responders and nonresponders differed significantly in SUVmax after ICT (postSUVmax , 6.0 vs 14.5; P < .001), resSUVmax (0.34 vs 0.81, P < .001), and resCT (0.71 vs 0.87, P = .004), but not in maximum tumor diameter after ICT (14 vs 20 mm, P = .11). resSUVmax <0.8 and absolute postSUVmax <10 provided the best discriminatory power for long-term success criteria (tumor-free survival, overall survival).Metabolic tumor response showed very good correlation with clinical tumor response to ICT. The value of metabolic response detected by (18) F-FDG-PET/CT should be explored in a prospective clinical trial. Cancer 2015;121:1214-1222. © 2014 American Cancer Society.
EVALuna2:13821

Spatial distribution of FoxP3+ and CD8+ tumour infiltrating T cells reflects their functional activity - Posselt, Rebecca; Erlenbach-Wuensch, Katharina; Haas, Matthias; Jeßberger, Jonas; Buettner-Herold, Maike; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Oncotarget, 2016)
Regulatory and cytotoxic T cells are key players in the host's anticancer immune response. We studied the spatial distribution of FoxP+ and CD8+ cells to identify potential interactions.In 202 patients 103 pre-radiochemotherapy biopsies and 153 post-radiochemotherapy tumour specimens of advanced rectal cancer were available and an immunohistochemical double staining of FoxP3+ and CD8+ tumour-infiltrating lymphocytes was performed to investigate cell density and cell-to-cell distances.FoxP3+ cells decreased after radiochemotherapy by a factor of 3 while CD8+ cells remained nearly unchanged. High epithelial (p=0.033) and stromal (p=0.009) FoxP3+ cell density was associated with an improved overall survival. Cell-to-cell distances of randomly distributed cells were simulated and compared to observed cell-to-cell distances. Observed distances shorter than the simulated, random distances were hypothesized to represent FoxP3+ cells actively interacting with CD8+ cells. Epithelial short distances were associated with a favourable prognosis while the opposite was true for the stromal compartment.The analysis of cell-to-cell distances may offer a tool to predict outcome, maybe by identifying functionally active, interacting infiltrating inflammatory cells in different tumour compartments.
EVALuna2:6815

Survey within the German Society for Radiation Oncology (DEGRO) on the Diagnosis and Treatment of Salivary Gland Carcinomas - Von Der Gruen, J.; Roedel, C.; Balermpas, P.; Martin, D.; Semrau, Sabine; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Targeted Therapy, Chemotherapy, Immunotherapy and Novel Treatment Options for Different Subtypes of Salivary Gland Cancer - Müller, Sarina Katrin; Haderlein, Marlen; Lettmaier, Sebastian; Agaimy, Abbas; Haller, Florian; Hecht, Markus; Fietkau, Rainer; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Surgical resection remains the first line treatment for salivary gland cancer (SGC). In the case of locally advanced disease, surgery is followed by adjuvant radiotherapy. Surgical resection should be favored in resectable locoregional recurrent disease as well, and even the complete resection of all distant oligometastases has clinical benefit for the patients. For inoperable and disseminated metastatic disease, a multitude of systemic therapies including chemotherapy, targeted therapy, and immunotherapy are available. In this review, the current therapeutic options for inoperable recurrent or metastatic SGCs are summarized. Systemic treatment can achieve prolonged progression-free and overall survival, while the overall prognosis remains poor. Current clinical trials include only a limited number of patients and mostly combine different histologic subtypes. Additionally, no randomized controlled trial comparing different therapeutic options has been performed. In the future, further studies with a larger patient cohort and ideally only one histologic subtype are needed in order to improve the outcome for SGC patients. However, this may be difficult to accomplish due to the rarity and diversity of the disease. Additionally, molecular analyses need to be performed routinely in order to individualize treatment and to go one step further towards precision medicine.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Acinic cell carcinoma; Adenoid cystic carcinoma; Chemotherapy; Immunotherapy; Mucoepidermoid carcinoma; Salivary duct carcinoma; Salivary gland cancer; Targeted therapy

The Prognostic Value of FoxP3+Tumour-Infiltrating Lymphocytes in Rectal Cancer Depends on Immune Phenotypes Defined by CD8+Cytotoxic T Cell Density - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Frontiers in Immunology, 2022)
Tumour-infiltrating FoxP3+ regulatory T cells have been identified as both positive and negative prognostic factors in colorectal cancer (CRC) and rectal cancer (RC). In this study we investigated whether immune phenotypes, defined by CD8+ cytotoxic T cell density, may influence the prognostic association of FoxP3+ T cell densities in RC. Tissue microarrays from 154 rectal cancer resections were immunohistochemically double stained for CD8 and FoxP3. CD8+ and FoxP3+ cell densities were measured in the stromal and intraepithelial compartment. Stromal FoxP3+ cell densities were not associated with 10-year overall survival (OS). In the "immune-desert" phenotype, defined by very low stromal CD8+ cell density, a high density of stromal FoxP3+ T cells displayed a tendency towards an association with decreased 10-year OS (p = 0.179). In "inflamed" tumours, defined by high intraepithelial CD8+ T cell infiltration, the opposite was the case and high stromal FoxP3+ T cell densities were a positive prognostic factor (p = 0.048). Additionally, patients with an increased FoxP3/CD8 cell density ratio demonstrated a strong trend towards decreased 10-year OS (p = 0.066). These contrasting findings suggest functional heterogeneity within the group of FoxP3+ T cells. They are consistent with experimental studies which reported suppressive and non-suppressive populations of FoxP3+ T cells in CRC. Furthermore, our study demonstrates that CD8 immunohistochemistry may act as an instrument to identify tumours infiltrated by possibly functionally differing FoxP3+ T cell subtypes.
CRIS-Team WoS Importer:2022-02-18

Therapies for synchronous malignomas - the importance of interdisciplinary oncology - Müller, Sarina Katrin; Haderlein, Marlen; Traxdorf, Maximilian; Semrau, Sabine; Agaimy, Abbas; Lettmaier, Sebastian; Gostian, Antoniu-Oreste; Schubart, Christoph; Mantsopoulos, Konstantinos; Schmidt, Daniela; Wiesmüller, Marco; Sievert, Matti; et al. (Laryngo-Rhino-Otologie, 2021)
CRIS-Team WoS Importer:2021-08-06

Treatment with (chemo)-radiation in old patients (≥76 years of age) with newly diagnosed non-metastatic squamous cell cancer of the head and neck region: real-world data from a tertiary referral center - Winkler, Leah-Sophie; Haderlein, Marlen; Semrau, Sabine; Putz, Florian; Höfler, Daniel; Müller, Sarina Katrin; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Schubert, Philipp (Frontiers in Oncology, 2024)
Purpose: Treatment of patients with cancer of the head and neck region is in focus in a multitude of studies. Of these patients, one patient group, those aged 76 and more, is mostly underrepresented despite requiring thorough and well-reasoned treatment decisions to offer curative treatment. This study investigates real-world data on curative treatment of old (≥76 years) patients with newly diagnosed squamous cell carcinoma of the head and neck region (HNSCC). Patients and methods: Between January 2010 and December 2021, we identified 71 patients older than 76 years with newly diagnosed HNSCC and cM0 at the Department of Radiation Oncology of the University Hospital of Erlangen-Nuremberg. Using electronic medical records, we analyzed treatment patterns and outcomes in terms of overall survival (OS), progression-free survival (PFS), and locoregional control (LRC) rate. Additionally, we performed univariate risk analysis and Cox regression in order to identify predictive factors associated with the abovementioned treatment outcomes. Results: The median follow-up was 18 months. OS was 83%, 79%, and 72% after 1 year, 2 years, and 3 years, respectively. PFS was 69%, 54%, and 46% after 1 year, 2 years, and 3 years, respectively. A total of 34 (48%) patients were treated with standard therapy according to current guidelines. The reasons for deviation from standard therapy before or during treatment were as follows: unfitness for cisplatin-based chemotherapy (n = 37), reduction of chemotherapy (n = 3), and dose reduction/interruption of radiotherapy (n = 8). Carboplatin-based systemic therapy showed improved PFS compared to cisplatin or cetuximab (60 vs. 28 vs. 15 months, p = 0.037) but without impact on OS (83 vs. 52 vs. 38 months, p = 0.807). Oropharyngeal tumor localization (p = 0.026) and combined treatment (surgery and postoperative treatment) (p = 0.008) were significant predictors for a better OS. In multivariate analysis, oropharyngeal tumor localization (p = 0.011) and combined treatment (p = 0.041) showed significantly increased PFS. After 1 year, 2 years, and 3 years, the cumulative incidence of locoregional recurrences (LRRs) was 13%, 24%, and 27%, respectively, and was significantly decreased in patients with oropharyngeal tumor localization (p = 0.037). Conclusions: Adherence to treatment protocols for radiotherapy alone in old patients with HNSCC is good, whereas the application of concurrent chemotherapy often deviates from guidelines in terms of de-escalation. An important risk factor for decreased OS, PFS, and a higher rate of LRR appears to be non-oropharyngeal tumor location in old patients.
CRIS-Team Scopus Importer:2024-05-24
Keywords: chemoradiation; head and neck cancer; old patients; squamous cell carcinoma; tumor localization

Use of NGS Gene Panel Analyzes for molecularly targeted System Therapy - Roesch, Johannes; Haller, Florian; Lettmaier, Sebastian; Haderlein, Marlen; Hartmann, Arndt; Moskalev, Evgeny; Tögel, Lars; Putz, Florian; Weissmann, T.; Schubert, P.; Höfler, Daniel; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02